The Problems of Broken Home toward Students' Mental and Achievement at Grade IV SDN 23 Lolong Padang Utara, Padang City - Indah Maharani; Nofriza Efendi; Ismul Rokif; Neli Putriah; Gingga Prananda (The Future of Education Journal, 2023)
This study aims to analyze how the Problems of Broken Home on Mental and Student Achievement in Grade IV at Public Alementary School 23 Lolong, North Padang District, Padang City. This research uses a qualitative approach with descriptive type. The subjects of this research are fourth grade teachers and students. This research was conducted at Public Alementary School 23 Lolong, North Padang District, Padang City in July 2022. The data collection techniques used were observation, interviews, and documentation. . The results showed that the problems of broken homes in students caused differences in interest in learning, which came from broken home families, but it cannot be denied that there are also some children who have a high interest in learning even though they come from broken home families. Parents and teachers have an important role in the mental and learning achievements of children, namely teachers must pay more attention to the learning of children who experience broken homes and parents must be able to establish good relationships with children even though they are divorced from their husbands or wives, because students who experience the impact of a broken home looking for someone or a friend who can provide motivation to be more enthusiastic in living life, and to have an interest in learning and learning achievement that is increasing than before and getting achievements in school